Towards CLIL-based international classes: Preparatory endeavours through training of English-mediated instruction - Rina Wahyu Setyaningrum; Riski Lestiono; Rosalin Ismayoeng Gusdian (Universitas Muhammadiyah Malang, 2025)
In today’s global era, the internationalization of educational institutions is crucial. SD Muhammadiyah 4 Kota Malang acknowledged this necessity and is committed to providing high-quality education by adapting international standards. To fulfill this commitment as well as to support Sustainable Development Goal (SDG) No. 4, the school aims to create an international learning environment where teachers and students use English for instructions. Content and Language Integrated Learning (CLIL) is a suitable approach for internationalizing education at this school, as it integrates subject learning with language development. This community service aimed to train and mentor teachers in using English effectively for international class preparation. The program focused on three key objectives: (1) enhancing teachers’ comprehension about CLIL, translanguaging, and trans-semiotizing concepts, (2) developing Classroom Passwords for all grade levels, and (3) implementing translanguaging and trans-semiotizing strategies. By understanding and applying CLIL, translanguaging, and trans-semiotizing, teachers can overcome anxiety about English use in the classroom. The teachers created verified Classroom Passwords which were registered for their intellectual property right and practiced translanguaging and trans-semiotizing in peer-teaching and real classroom settings as well as in virtual environment using Virtual Reality (VR).